Cote d'Ivoire : Enhanced Initiative for Heavily Indebted Poor Countries; Decision Point Document. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper examines Cote d'Ivoire's debt sustainability analysis undertaken in connection with the Enhanced Initiative for Heavily Indebted Poor Countries. The crisis years led to a substantial increase in poverty and deterioration in living standards. The March 2007 Ouagadougou Political Accord provides a roadmap for reunification, national reconciliation, demobilization, and elections. Significant revenue efforts and overall expenditure restraint have resulted in a modest space for social and crisis-exit spending. To eliminate extrabudgetary spending in the future and enhance transparency, the authorities have established a range of safeguards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet